Characterization of patients operated on for non-syndromic craniosynostosis. Villa Clara, 2018-2022 - Miguel Ángel Cruz Díaz; Ángel Serafín Camacho Gómez; Carlos Javier Artiles Rivero; Ramón Sarduy Arana (Medisur)
Background: craniosynostosis is one of the most frequent neurosurgical pathologies in the pediatric age. Knowledge about its management is of vital importance to intervene with treatment in a timely manner. Objective: to characterize the patients operated on for non-syndromic craniosynostosis. Methods: a descriptive and cross-sectional study was carried out, from January/2018 to December/2022, with all the patients operated on for craniosynostosis at the José Luis Miranda Pediatric Hospital, in Villa Clara (N=28). The analyzed variables were: sex, skin color, classification of the malformation according to the affected suture, symptoms and signs associated with the malformation, age at surgery, surgical technique, and complications. Results: a predominance of the male sex and patients with white skin color was observed. The most frequent form of presentation was scaphocephaly, and it was associated with symptoms such as delayed psychomotor development and strabismus. The surgical techniques performed were total remodeling of the cranial vault, which in most children was performed before 23 months old. The most frequent complication was infection of the surgical wound. Conclusions: craniosynostosis is a frequent neurosurgical pathology in the male sex. The most frequent form of presentation is scaphocephaly and it can be associated with neurological symptoms and signs. Surgical techniques performed for remodeling of the cranial vault must be performed before the first year of life, in order to reduce the complications rate.